2018
DOI: 10.3389/fmars.2018.00488
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Prochlorococcus Diversity and Photoacclimation During Short-Term Shifts in Water Column Stratification at Station ALOHA

Abstract: The cyanobacterium Prochlorococcus is the dominant phototroph in surface waters of the vast oligotrophic oceans, the foundation of marine food webs, and an important component of global biogeochemical cycles. The prominence of Prochlorococcus across the environmental gradients of the open ocean is attributed to its extensive genetic diversity and flexible chlorophyll physiology, enabling light capture over a wide range of intensities. What remains unknown is the balance between temporal dynamics of genetic div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
(99 reference statements)
4
20
0
Order By: Relevance
“…254Amplicon sequencing of the Internal Transcribed Spacer between the 16S and 23S genes (ITS, 255(Thompson et al 2018)) revealed that between ~100-137m LL cells (belonging primarily to the LL-I and 256 LL-IV clades) gradually replace the HL cells, consistent with previous studies (e.g. (Malmstrom et al 257 2010)) but contrasting with the sharp delineation between high-chlorophyll and low-chlorophyll 258Prochlorococcus populations (Fig.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…254Amplicon sequencing of the Internal Transcribed Spacer between the 16S and 23S genes (ITS, 255(Thompson et al 2018)) revealed that between ~100-137m LL cells (belonging primarily to the LL-I and 256 LL-IV clades) gradually replace the HL cells, consistent with previous studies (e.g. (Malmstrom et al 257 2010)) but contrasting with the sharp delineation between high-chlorophyll and low-chlorophyll 258Prochlorococcus populations (Fig.…”
supporting
confidence: 84%
“…However, when co-cultured with a heterotrophic 188 bacterium, Alteromonas HOT1A3, all Prochlorococcus strains were able to re-grow after 60 days of N 189 stress. Interestingly, strain MIT9313, which was initially inhibited by this Alteromonas strain ( Figure 4A consists of both HL and LL cells, implying that phenotypic heterogeneity (acclimation) can also 245 contribute to this phenomenon (Thompson et al 2018). We therefore asked whether the double 246 population could also be due to the presence of chlorotic cells, e.g.…”
Section: Evaluating the Viability Of Sub-populations 169mentioning
confidence: 97%
See 1 more Smart Citation
“…Using this method, we observed bimodal size distributions in Prochlorococcus , which were not apparent in flow cytograms; however, it is likely that traditional flow cytometers do not sufficiently discriminate anisotropic scatterers in this size range to resolve peaks which are separated by only 0.15 μ m. For Prochlorococcus , this distribution may either be due to the cell cycle stage distribution (this interval corresponds to a 1.8‐ to 2.6‐fold fold change in cell volume) or due to physiological differences between strains. The latter has been observed at Station ALOHA, especially near the deep chlorophyll maximum depth (Campbell and Vaulot ) or following a deepening of the mixed layer, which transiently mixes the low‐light adapted and high‐light adapted Prochlorococcus populations (Thompson et al ); however, these bimodal distributions are more prominent in flow cytograms rather than the subtle differences we observed.…”
Section: Discussionmentioning
confidence: 45%
“…In the oligotrophic ocean north of the Hawaiian Islands, Prochlorococcus is the numerically dominant photosynthetic organism (98% of fluorescent particles). Within the upper 100 m, the distribution of Prochlorococcus DNA ecotypes is relatively constant . Yet, chlorophyll fluorescence and low‐angle scatter measurements show a steady increase as one descends down the water column.…”
mentioning
confidence: 99%